Hyperdictionary: a knowledge discovery tool to help information retrieval - Wives, L.K.; Loh, S. (String Processing and Information Retrieval: A South American Symposium, Santa Cruz de la Sierra, Bolivia, September 9-11, 1998, 1998)
We present a knowledge discovery tool to help the information retrieval process. This tool, which we define as Hyperdictionary, is capable of acquiring and holding relationships among words to describe the context of some information-the knowledge about some subject. This knowledge is then used to retrieve information by contextual search in a document collection. Our preliminary studies indicate that this structure can be used in conjunction with some information retrieval tool, to aid the user in the elaboration of his query. The user's query is automatically expanded with words strongly related to the information the user is wanting, facilitating the retrieval process.